Hubungan Pola Tidur dengan Risiko Diabetes Tipe 2 pada Dewasa Muda : Relationship between Sleep Patterns and the Risk of Type 2 Diabetes in Young Adults - Nurachma, Evy; Hanim, Hamidah; Winarningsih, Rahayu Arum; Gomes, Margaretha Bernadete (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
The increasing prevalence of Type 2 Diabetes Mellitus (T2DM) among young adults is closely associated with lifestyle changes and sleep disturbances. Poor sleep patterns contribute to impaired glucose regulation and an elevated risk of diabetes. This study aimed to examine the effectiveness of sleep hygiene management interventions in reducing the risk of T2DM among young adults. A quasi-experimental study employing a nonequivalent control group design was conducted involving 60 participants, divided into an experimental group (n = 30) and a control group (n = 30). The experimental group received an eight-week sleep hygiene intervention, while the control group maintained their usual routines. The variables measured included fasting blood glucose levels and sleep quality assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the independent samples t-test. The results demonstrated that the experimental group experienced a significant reduction in fasting blood glucose levels by 15.42 mg/dL and an improvement in sleep quality by 6.28 points, with statistical significance at p < 0.001. In contrast, the control group showed no significant changes.  In conclusion, sleep hygiene management interventions are effective non-pharmacological strategies for reducing the risk of Type 2 Diabetes Mellitus among young adults.